Critical Mode Switching of Flexible-Cantilever Flutter in Low-Reynolds-Number Channel Flow - Cisonni, Julien; Lucey, Anthony; Elliott, N. (2016)
Inviscid flow modelling has predominantly been employed in the numerous studies on flow-induced flutter instability of flexible cantilevers. This approach has been supported by the prevailing characteristics, giving high Reynolds numbers, of such fluid–structure interaction (FSI) systems in the wide range of engineering applications. By contrast, in this paper, a numerical model coupling a one-dimensional elastic beam model to the Navier–Stokes equations is used to determine the linear flutter-instability characteristics of a slender flexible cantilever immersed in two-dimensional viscous channel flow for laminar flow conditions. The results show that the FSI instability boundaries and the pre- and post-critical cantilever motion can be significantly altered by the non-negligible contribution of viscous effects to the hydrodynamic forces. In general, this model predicts that the FSI system becomes more stable for Reynolds numbers (based on channel height) lower than 100. For cases within this range of very low Reynolds numbers, this study focuses on the particular fluid-to-solid mass ratios at which viscous effects can possibly lead to a change in the critical mode that first becomes unstable.